Fumed silica-coated magnetic particles: DNA extraction application - Stanley Evander Emeltan TJOA; Mudasir MUDASIR; Edi SUHARYADI; Budi Setiadi DARYONO (Studia Universitatis Babeș-Bolyai. Biologia, 2025)
Tetraethyl orthosilicate (TEOS) is widely used for preparing magnetic particles in DNA extraction kits, but it poses toxicity and safety concerns. To address this issue, we developed magnetic particles using fumed silica as a safer alternative to TEOS for magnetite particle preparation for DNA extraction. The method effectively extracts DNA from various biological matrices, including urine, serum, saliva, sputum, whole blood, and plasma, without detectable inhibitors. The extracted DNA is suitable for downstream molecular applications such as qPCR and sequencing. The proposed magnetic particles with fumed silica not only reduce chemical hazards but also provide a safer, efficient, and reliable method for routine DNA extraction in molecular biology laboratories.